Making Halal Food in Processed Fish: From Traditional Knowledge to Fishermen’s Household Awareness in Producing Fish-Processed Halal Food - Darvina Soedarwo, Vina Salviana; Saati, Elfi Anis (Institut Agama Islam Negeri Madura, 2018)
The daily life of the fishermen’s household in Lekok Pasuruan, East Java, Indonesia is still adopting traditional knowledge, especially in their activities in catching and processing fishes. This knowledge is inherited from generation to the next. However, at present they have started making entrepreneurial endeavors although the endeavors are still limited to producing processed fishes in the form of fried fishes that are sold in the nearest markets. The problem encountered by the fishermen community is the stagnation of their welfare due to their relatively low incomes. Therefore, it is necessary to study the problem and also to guide them in solving the problem. The method of this research is a Participatory Action Research (PAR) and using Rapid Rural Apraisal (RRA) approach. The findings of the research is a model for empowering the fishermen’s household. This model is named integrative-participative model with entrepreneurial mindset approach. By using the model, the fishermen’s household will be more aware of the weightiness of fish-processed food variations and halal certification for the product that may improve the consumers’ interest in buying the products.